Effect of magnetic field intensity on the microstructure and abrasion resistance of magnetic electrodeposited Ni–Co–SiC thin films. Issue 1 (1st January 2023) - Dong, Xiaowei; Yin, Bo; Zhu, Chunyan; Wang, Ming; Li, Weikai; Li, Qingda
Abstract: The purpose of this work is intended to fabricate Ni–Co–SiC thin films on the surface of carbon steel bearing by magnetic electrodeposition (MED) technique. The surface morphology and composition of Ni–Co–SiC thin films were investigated by scanning electron microscope (SEM), energy disperse spectroscopy (EDS), and X-ray diffraction (XRD). The microhardness and frictional coefficient were detected by utilizing microhardness tester and ball-on-desk wear tester. The surface protrusion of Ni–Co–SiC thin films presented first descent and then ascent with the increasing magnetic field intensity. The surface morphology of Ni–Co–SiC thin films obtained at magnetic field intensity of 0.8 T presented more flat and dense than those deposited at magnetic field intensity of 0.4 and 1.2 T. Meanwhile, the highest microhardness of 987.5 Hv and lowest frictional coefficient of 0.75 were also emerged in the Ni–Co–SiC thin films fabricated at magnetic field intensity of 0.8 T. In addition, XRD results indicated the Ni–Co–SiC thin films manufactured at magnetic field intensity of 0.8 T possessed smallest Ni–Co grain size of 15.6 nm. The abrasion loss of M2 thin film was 17.3 mg, while the M1 film processed the largest abrasion loss of 31.5 mg. In addition, the average frictional coefficients of M1, M2 and M3 thin films were 1.04, 0.75 and 0.85, respectively.